Increasing proportion of herpes simplex virus type 1 among women and men diagnosed with first-episode anogenital herpes: a retrospective observational study over 14 years in Melbourne, Australia. (15th December 2018) - Durukan, Duygu; Fairley, Christopher K; Bradshaw, Catriona S; Read, Tim R H; Druce, Julian; Catton, Michael; Caly, Leon; Chow, Eric P F
Abstract : Objectives: Reports of rising herpes simplex virus type 1 (HSV-1) genital infections relative to HSV-2 have been published up to 2006 in Australia. These changes have been attributed to declining childhood immunity to HSV-1. We described the temporal trends of HSV-1 and HSV-2 up to 2017 in Melbourne, Australia, to determine if the earlier trend is continuing. Methods: We conducted a retrospective review of the medical records of 4517 patients who were diagnosed with first episode of anogenital HSV infection at the Melbourne Sexual Health Centre, Australia, between January 2004 and December 2017. HSV-1 and HSV-2 were calculated as a proportion of all first episode of anogenital HSV infections. The change in the proportions of HSV-1 and HSV-2 over time was assessed by a χ 2 trend test. Risk factors associated with HSV-1 were examined using a multivariable logistic regression model. Results: The proportion of first episode of anogenital herpes due to HSV-1 increased significantly over time in women (from 45% to 61%; ptrend <0.001) and heterosexual men (from 38% to 41%; ptrend =0.01) but not in men who have sex with men (MSM) (ptrend =0.21). After adjusting for condom use, partner number and age, the annual increase remained significant only in women (OR 1.08, 95% CI 1.03 to 1.13, p<0.001). In MSM, HSV-1 caused up to two-thirds of anogenital herpes in most years and HSV-1 was more likely to be diagnosed at an anal site than genital site (OR 1.69, 95% CI 1.23 to 2.32, p<0.001). Younger age (<28 years) was an independent risk factor for HSV-1 in all groups. Conclusions: The proportion of first-episode anogenital herpes due to HSV-1 has been rising in women since 2004. HSV-1 has become the leading cause of anogenital herpes in younger populations, women and MSM.